Forwarding cooperativism a global challenge : papers presented at the 1st Asia-Pacific Conference of Cooperatives putting a human face to globalization : the cooperative model - Aganon, Marie E.; Mercado, Rosalinda C. ([Centralbooks Supply] Center of Labor and Grassroots Initiatives, School of Labor and Industrial Relations, University of the Philippines, 2008)
"The papers herein present the many ways in which cooperatives have been beneficial to various sectors, such as: as a tool to translate the intents of agrarian reform; as a safety net for unionized workers; as an employee benefit mechanism; as an instrument of the state for socialist transformation; as a poverty alleviation and employment generation scheme; as an organization for lifelong learning; [and] as a prototype for the emerging model of workers' cooperatives."--Preface.